2011
DOI: 10.1111/j.1365-313x.2011.04622.x
|View full text |Cite
|
Sign up to set email alerts
|

Pepper asparagine synthetase 1 (CaAS1) is required for plant nitrogen assimilation and defense responses to microbial pathogens

Abstract: SUMMARYAsparagine synthetase is a key enzyme in the production of the nitrogen-rich amino acid asparagine, which is crucial to primary nitrogen metabolism. Despite its importance physiologically, the roles that asparagine synthetase plays during plant defense responses remain unknown. Here, we determined that pepper (Capsicum annuum) asparagine synthetase 1 (CaAS1) is essential for plant defense to microbial pathogens. Infection with Xanthomonas campestris pv. vesicatoria (Xcv) induced early and strong CaAS1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 54 publications
6
79
0
1
Order By: Relevance
“…This finding is in agreement with that observed for other Arabidopsisinfecting viruses, such as Cabbage leaf curl virus, Cucumber mosaic virus, and Turnip mosaic virus (Marathe et al, 2004;Yang et al, 2007;Hwang et al, 2011). It is not clear, however, whether elevated amino acid levels in infected leaves are due to selective protein breakdown in this tissue or higher rates of biosynthesis.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in agreement with that observed for other Arabidopsisinfecting viruses, such as Cabbage leaf curl virus, Cucumber mosaic virus, and Turnip mosaic virus (Marathe et al, 2004;Yang et al, 2007;Hwang et al, 2011). It is not clear, however, whether elevated amino acid levels in infected leaves are due to selective protein breakdown in this tissue or higher rates of biosynthesis.…”
Section: Discussionsupporting
confidence: 88%
“…This result is consistent with the report by Lim et al [9]. Many studies have also demonstrated a role of amino acids in the establishment of resistance against plant pathogens [46] [48] [53], and that the alteration of specific metabolite levels by feeding or genetic manipulation of plant metabolic pathways can lead to resistance against pathogens. Grenville-Briggs et al [54] identified that the biosynthesis of many amino acids was up-regulated in plants by fungi and oomycetes during biotrophic growth and also reported that genes involved in the biosynthesis of methionine, tryptophan, threonine, and branched-chain amino acids were up-regulated in plants after infection.…”
Section: Amino Acid Changes From Different Treatment Groupssupporting
confidence: 83%
“…7 For instance, an early (5 hpi) induction of AS1 in pepper was shown to be involved in resistance against the hemibiotrophic bacterial pathogen Xanthomonas campestris pv vesicatoria, while later (15-20 hpi) induction of the enzyme (during the necrotrophic phase of the pathogen infection) was associated with susceptibility. 8 Taking advantage of the abscisic acid (ABA)-deficient sitiens mutant of tomato, which displays high levels of immunity against the necrotrophic fungus Botrytis cinerea (B. cinerea), [9][10][11] our research aims to decipher the molecular underpinnings of necrotroph resistance in plants. In our latest study, we showed that the observed resistance response in sitiens is dependent on timely restructuring of the central C/N metabolism, particularly the GABA-shunt.…”
Section: Resultsmentioning
confidence: 99%